Implementation signal processing functions on portable devices - Ng, Jing Yang. (2013)
Final Year Project is a one-year project designed by Nanyang Technological University which aims to give final year students who are going to graduate an opportunity to explore deeper in their interest field and provide them significant skills and experiences needed for professional working environments. Furthermore, it may help students to be more aware of their career selection.